Operons Are a Conserved Feature of Nematode Genomes. Issue 4 (1st August 2014) - Pettitt, Jonathan; Philippe, Lucas; Sarkar, Debjani; Johnston, Christopher; Gothe, Henrike Johanna; Massie, Diane; Connolly, Bernadette; Müller, Berndt
Abstract: The organization of genes into operons, clusters of genes that are co-transcribed to produce polycistronic pre-mRNAs, is a trait found in a wide range of eukaryotic groups, including multiple animal phyla. Operons are present in the class Chromadorea, one of the two main nematode classes, but their distribution in the other class, the Enoplea, is not known. We have surveyed the genomes of Trichinella spiralis, Trichuris muris, and Romanomermis culicivorax and identified the first putative operons in members of the Enoplea. Consistent with the mechanism of polycistronic RNA resolution in other nematodes, the mRNAs produced by genes downstream of the first gene in the T. spiralis and T. muris operons are trans -spliced to spliced leader RNAs, and we are able to detect polycistronic RNAs derived from these operons. Importantly, a putative intercistronic region from one of these potential enoplean operons confers polycistronic processing activity when expressed as part of a chimeric operon in Caenorhabditis elegans . We find that T. spiralis genes located in operons have an increased likelihood of having operonic C. elegans homologs. However, operon structure in terms of synteny and gene content is not tightly conserved between the two taxa, consistent with models of operon evolution. We have nevertheless identified putative operons conserved between Enoplea and Chromadorea. Our data suggest that operons and "spliced leader" (SL) trans -splicing predate the radiation of the nematode phylum, an inference which is supported by the phylogenetic profile of proteins known to be involved in nematode SL trans -splicing.